A comparison of EuroQol 5-Dimension health-related utilities using Italian, UK, and US preference weights in a patient sample - Mozzi A; Meregaglia M; Lazzaro C; Tornatore V; Belfiglio M; Fattore G (Dove Medical Press, 2016)
Adelaide Mozzi,1 Michela Meregaglia,2 Carlo Lazzaro,3 Valentina Tornatore,4 Maurizio Belfiglio,4 Giovanni Fattore,1,2 1Department of Policy Analysis and Public Management, 2Centre for Research on Health and Social Care Management (CeRGAS), Bocconi University, 3Studio di Economia Sanitaria, Milan, 4AbbVie srl, Campoverde Di Aprilia, Latina, Italy Abstract: Weights associated with the EuroQol 5-Dimension 3-Level (EQ-5D-3L) instrument represent preferences for health states elicited from general population's samples. Weights have not been calculated for every country; however, empirical research shows that cross-country differences exist. This empirical study aims at investigating the impact of recently developed Italian weights in comparison with UK and US scores on health-related utility calculation using a sample of patients with Crohn's disease. The study is based on a survey on health-related quality of life in patients (n=552) affected by active Crohn's disease conducted in Italy from 2012 to 2013. Utilities computed through the Italian algorithm (mean: 0.76; SD: 0.20; median: 0.81) are generally higher than US (mean: 0.69; SD: 0.22; median: 0.77) and UK (mean: 0.57; SD: 0.32; median: 0.69) utilities, except for extremely severe health states where US values outweigh the Italian ones. UK preference weights generate the highest number of negative results. All the three value distributions are left-skewed due to very low scores associated with the most serious health states (ie, three or four levels equal to 3). As expected, despite the tariff set considered, more severe disease (Harvey Bradshaw Index >16) reduces the mean conditional EQ-5D-3L index (P<0.0001). Kendall's rank correlation between EQ Visual Analog Scale score and EQ-5D-3L index is positive (P<0.0001), even though patients tend to value their health-related quality of life more when responding to EQ-5D-3L questions than on EQ Visual Analog Scale. Regardless of the tariff set considered, ordinary least-square results highlight that more severe disease (Harvey Bradshaw Index >16) reduces the mean conditional EQ-5D-3L index (P<0.0001). Results reveal remarkable differences among the three national tariff sets and especially when severe health states occur, suggesting the need for country-specific preference weights when evaluating utilities, which can be problematic since they have not been calculated for every country yet. Keywords: EQ-5D, preference weights, utility values, VAS, Crohn's disease